Somatic embryogenesis in yam (dioscorea rotundata) (2011)
Embryogenic yam (Dioscorea rotundata) cultures were induced from petioles of leaves of in vitro grown plants on medium supplemented with different 2.4-D concentrations. Cultures were maintained either on semisolid or in liquid MS medium supplemented with 4.52 μM 2.4-D. The effect of sucrose concentration on somatic embryo development was also evaluated and the effects of different BAP concentrations on somatic embryo conversion were determined. Treatments were distributed using a complete randomized design. The highest rate of induction occurred with 4.52 μM 2.4-D. Sucrose at 131.46 mM significantly enhanced somatic embryo development. The conversion rate was not affected by BAP.